PERAN GURU DALAM MENGEMBANGKAN KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN (Penelitian Kualitaif di RA FIRDAUS I Serang) - Dila Muliati; Alis Triena Permanasari; Tri Sayekti (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2017)
Early childhood is a small human being that has the potential to be developed. Speaking is one of the first science learned by humans in life. Speaking is also a form of language that uses the articulation of words used to convey meaning, because speaking is the most effective form of communication, its use is most widespread and important. This research is very useful 1) to know the development of the relationship of children aged 5-6 years in RA FIRDAUS, 2) the role of teachers in developing speaking skills in children aged 5-6 years in RA FIRDAUS, 3) methods used by teachers in developing speaking skills in children aged 5-6 years in RA FIRDAUS. This research was conducted at RA FIRDAUS I in April 2016. The method used in this research is qualitative method with descriptive research type. Flavor data through observation, interviews, and documentation. As a result of this research, namely: the development of children's speech in RA FIRDAUS I speech ability has many well developed, seen from the activity of children who always follow the learning activities with the spirit in the method of learning questions and answers the children are always confident to speak and berdok in front of the class. The role of teachers in developing the ability to speak can be seen through the method of learning by the teacher is the method of question and answer at the beginning and end of activities, with this method teachers can encourage children to always ask. The method given by the teacher in developing the children's speech ability of the question and answer method can encourage the child to always ask, the method of conversation can accustom the child to communicate with the teacher and peers and can establish the closeness between teacher and child, the learning method can increase the child's knowledge about new who are not yet children and can increase the involvement of children in activities, and methods so that children can quickly understand and do what the teacher has demonstrated.